Does European Union and national regional policy correlate with a decrease in unemployment rate in Romania? - Gorda, Diana (2015)
The bachelor thesis aims at answering the question if the regional and European Union Cohesion policy correlates with a decrease in unemployment rate in Romania. The thesis starts the analysis with a controversial theoretical background, including the convergence and divergence views and the related economic theories, as Solow and AK models. The study proceeds to a short description of the Cohesion Policy, its funds and targeted aims. The bachelor thesis then analyses the challenges of the Romanian labor market, the reasons that bring to a non-competitive labor environment, and further on focuses on the vulnerable groups of population most affected by unemployment. At the same time, at this section the paper provides a final distinction between two time horizons: before joining and after joining the European Union. The last part of the research is composed of an empirical work concerning Cohesion policy funding and the effectiveness on a macroeconomic indicator, as unemployment. The correlation between unemployment rate and Cohesion Policy is found to be negative, as expected from the theoretical background.